Genome-Scale Analysis of the WRI-Like Family in Gossypium and Functional Characterization of GhWRI1a Controlling Triacylglycerol Content - Xinshan Zang; Wenfeng Pei; Man Wu; Yanhui Geng; Nuohan Wang; Guoyuan Liu; Jianjiang Ma; Dan Li; Yupeng Cui; Xingli Li; Jinfa Zhang; Jiwen Yu (Frontiers in Plant Science, 2018)
Cotton (Gossypium spp.) is the most important natural fiber crop and the source of cottonseed oil, a basic by-product after ginning. AtWRI1 and its orthologs in several other crop species have been previously used to increase triacylglycerols in seeds and vegetative tissues. In the present study, we identified 22, 17, 9, and 11 WRI-like genes in G. hirsutum, G. barbadense, G. arboreum, and G. raimondii, respectively. This gene family was divided into four subgroups, and a more WRI2-like subfamily was identified compared with dicotyledonous Arabidopsis. An analysis of chromosomal distributions revealed that the 22 GhWRI genes were distributed on eight At and eight Dt subgenome chromosomes. Moreover, GhWRI1a was highly expressed in ovules 20–35 days after anthesis and was selected for further functional analysis. Ectopic expression of GhWRI1a rescued the seed phenotype of a wri1-7 mutant and increased the oil content of Arabidopsis seeds. Our comprehensive genome-wide analysis of the cotton WRI-like gene family lays a solid foundation for further studies.